PENERAPAN KONSEP REGIONALISME PADA PERANCANGAN CITY HOTEL BINTANG EMPAT DI KOTA PATI - Faisal - Darmawan (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2022)
Indonesia's development in the economic field continues to increase from year to year, this triggers business people to travel from one city to another to do business activities, especially in Pati City. This activity has the potential to design a Four Star City Hotel in Pati City. The design of a Four Star City Hotel in Pati City is an inn to accommodate the need to stop by business people so that they can support their business activities. City Hotel can also be a means of meeting for business people who want to do business activities so that the quality of their meetings will be well facilitated. Research methods used by analyzing treads, space programs, structures, utilities so as to give rise to a design concept of regionalism architectural approach that can be a solution to bring about local cultural locality designs such as brass materials, roof shapes that resemble royal crowns and the philosophy of the Pati City Regency logo applied to the design such as, green layout elements, water and wood parquet materials so as to represent the City. Starch. The conclusion of this design is to design a city hotel as a place to stop and do business in the city of Pati that raises the cultural locality of Pati City so that it can become a new icon that is easily remembered by residents of Pati City and hotel visitors who come.